2009
DOI: 10.1111/j.1440-172x.2009.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors influencing knowledge transfer into practice in Iranian nursing context: A grounded theory approach

Abstract: 15: 426-436 Organizational factors influencing knowledge transfer into practice in Iranian nursing context: A grounded theory approachDivergence in Iranian nursing organization including academic and clinical settings adversely affects knowledge transfer. Centralized and medical focused nursing with a lack of effective representation at senior or national level was inferred as the main causal conditions. Using grounded theory methodology, in-depth individual interviews were conducted with 17 participants to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A brief look at the Iranian studies of nursing practice shows that the Iranian health‐care services suffer from a low quality of nursing care . Moreover, nurses experience uncertainty in clinical practice, and many personal and organizational factors hinder the transference of knowledge into clinical practice Evidence‐based practice (EBP) is an approach that potentially handles clinical issues effectively and can lead to better care . Because diabetic foot disease is the main cause of non‐traumatic amputation of lower extremities, early recognition and management of foot complications could prevent amputations and other adverse outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…A brief look at the Iranian studies of nursing practice shows that the Iranian health‐care services suffer from a low quality of nursing care . Moreover, nurses experience uncertainty in clinical practice, and many personal and organizational factors hinder the transference of knowledge into clinical practice Evidence‐based practice (EBP) is an approach that potentially handles clinical issues effectively and can lead to better care . Because diabetic foot disease is the main cause of non‐traumatic amputation of lower extremities, early recognition and management of foot complications could prevent amputations and other adverse outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…The literature has argued that the factors that influence knowledge application include absorptive capacity (Al-Salti et al, 2010), trust (Gupta and Govindarajan, 2000), culture (Karlsen and Gottschalk, 2004), reward (Evaristo, 2005), willingness to apply knowledge (Liyanage et al, 2009) and expertise (Salsali et al, 2009). Among these factors, the study found trust, culture and absorptive capacity as the critical factors in knowledge application in Ghanaian industries, confirming the findings of Gupta Note: The means are determined by using a five-point Likert scale rating from strongly agree (5) to strongly disagree (1).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Again the factors explored are only representative but not exhaustive. Other researchers (Tan, 2009;Salsali et al, 2009) have found expertise and Information Technology as factors that affect knowledge application. Future studies must incorporate these other factors.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…Thus, characteristics of centralized structures particularly superior's high monitoring are conspicuous, and physicians have long been in charge of all matters related to healthcare. Results of a study by Salsali et al (2009) on organizational factors affecting knowledge transfer into practice in Iranian nursing context depict that ineffectual organizational structure especially hierarchy of authority was one of the barriers to knowledge transfer into practice. Boswell et al (2005) also verify that, the sense of powerlessness is one of the barriers to nurses' participation.…”
Section: Discussionmentioning
confidence: 99%